Characterizing the functioning of the attentional networks in state and trait anxiety: the role of affective information - Pacheco-Unguetti, Antonia Pilar; Acosta, Alberto; Lupiáñez, Juan (Frontiers in Psychology, 2025)
IntroductionThe aim of the present research was to examine the role of affective information in the functioning of attentional networks in individuals with high vs. low trait or state anxiety. Previous studies suggest that anxiety can influence attentional processes, but the impact of affective information, such as alerting emotional stimuli, on these attentional networks remains unclear.MethodsWe conducted a set of experiments using negative or neutral faces as alerting stimuli, presented either alone or together with a neutral sound, within a modified version of the Attention Network Test-Interactions (ANT-I). Additionally, data from previous experiments with similar anxiety groups and without affective manipulations of alertness were analyzed for comparative insights (378 participants in total).ResultsResults showed three main effects on the functioning of attentional networks when affective alerting signals were introduced: (1) the alertness effect is increased, (2) the interference effect is increased, and (3) the orienting effect is decreased. These effects occurred regardless of the valence of the alerting stimuli on a given trial. Importantly, the presence of affective information on some trials eliminated the group differences regarding the functioning of the attentional networks that are usually found when no affective information is presented. Specifically, the larger interference effect commonly observed in individuals with high trait-anxiety and the larger alertness and orienting effects seen in those with high state-anxiety, disappeared when emotional alerting stimuli were included.DiscussionThe findings suggest that emotional information can significantly impact the functioning of attentional networks, particularly in relation to anxiety. The presence of affective stimuli seems to modulate attentional biases associated with anxiety, potentially neutralizing the usual effects seen in individuals with high trait or state anxiety. The role of affective information on the functioning of the attentional networks is discussed within the framework of anxiety and attention.